2006
DOI: 10.1017/s0031182006000035
|View full text |Cite
|
Sign up to set email alerts
|

Microfilarial distribution of Loa loa in the human host: population dynamics and epidemiological implications

Abstract: S U M M A R YSevere adverse events (SAEs) following ivermectin treatment may occur in people harbouring high Loa loa microfilarial (mf) densities. In the context of mass ivermectin distribution for onchocerciasis control in Africa, it is crucial to define precisely the geographical distribution of L. loa in relation to that of Onchocerca volvulus and predict the prevalence of heavy infections. To this end, we analysed the distribution of mf loads in 4183 individuals living in 36 villages of central Cameroon. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…This relationship has been explained by suggesting that the degree of parasite overdispersion among hosts (probably driven by heterogeneous exposure to infection) decreases as mean infection intensity rises, allowing for infection prevalence to reach high values (nearly 100%) when intensity is high. Interestingly, previous studies have suggested that the degree of L. loa overdispersion across communities is severe and does not change with mean infection intensity [69], an observation that could lead to the lower levels (50-60%) of saturating microfilarial prevalence that have been reported.…”
Section: Prevalence and Intensity Of Infection In Human Populationsmentioning
confidence: 90%
“…This relationship has been explained by suggesting that the degree of parasite overdispersion among hosts (probably driven by heterogeneous exposure to infection) decreases as mean infection intensity rises, allowing for infection prevalence to reach high values (nearly 100%) when intensity is high. Interestingly, previous studies have suggested that the degree of L. loa overdispersion across communities is severe and does not change with mean infection intensity [69], an observation that could lead to the lower levels (50-60%) of saturating microfilarial prevalence that have been reported.…”
Section: Prevalence and Intensity Of Infection In Human Populationsmentioning
confidence: 90%
“…For randomly distributed microfilariae, a Poisson distribution would be appropriate. However, it is likely that there is ' clumping ' of microfilariae in the skin (Kershaw, Duke and Budden, 1954), leading to an excess of zeros in comparison with the Poisson distribution (Grenfell et al 1990 ;Pion et al 2006). We have chosen to model the observed distribution of microfilariae with a zero-inflated Poisson distribution.…”
Section: Expected Microfilarial Load Within An Individual Hostmentioning
confidence: 99%
“…To address this problem we first develop a model for the variation in parasite count between individuals within a community, and explore how the parameters of this distribution co-vary with each other and with community-level covariates.This study builds on previous work which also looked at the distribution of Loa loa microfilarial loads in communities [11]. In contrast to this earlier work, we allow the relationship between community-level prevalence and mean intensity of infection to vary stochastically between communities.…”
Section: Introductionmentioning
confidence: 99%